(untitled) (Swiss Medical Weekly, 2010)
The plasticity and self-regenerative properties of stem cells have opened new avenues in regenerative medicine. Greater understanding of the biology of stem cells is followed by growing expectations of a rapid translation into alternative therapeutic options. Recent preclinical studies and clinical trials employing stem and progenitor cells from different sources have shown encouraging results. However, their underlying mechanisms are still poorly understood, the potential adverse effects and the discrepancy in efficacy remain to be further investigated. Their essential role in vessel regeneration has made endothelial progenitor cells (EPC) a suitable candidate for therapeutic applications aiming at tissue revascularisation. Recent evidence suggests that EPC contribute to neovascularisation not only by direct participation in tissue homeostasis but mainly via paracrine mechanisms. In future, novel therapeutic strategies could be based on EPC paracrine factors or synthetic factors, and replace cell transplantation.